Long-term rotation and tillage effects on soil structure and crop yield - Munkholm, Lars J.; Heck, Richard J.; Deen, Bill (Soil & tillage research, 2013)
► Positive effect of diverse rotation on soil structural quality. ► Diverse crop rotation needed for optimal performance of no tilled soil. ► Crop yield correlated significantly with the visual soil structure scores. Tillage and rotation are fundamental factors influencing soil quality and thus the sustainability of cropping systems. Many studies have focused on the effects of either tillage or rotation, but few have quantified the long term integrated effects of both. We studied the issue using a 30-year old long-term rotation and tillage treatment experiment on a Canadian silt loam soil. Topsoil measurements were carried out for three different rotations: R1, (C–C–C–C) continuous corn (Zea mays L.), R6, (C–C–O(RC), B(RC)) corn, corn, oats (Avena fatua L.) and spring barley (Hordeum vulgare L.) and R8, (C–C–S–S) corn, corn, soybean (Glycine max L.), soybean. A red clover (Trifolium pretense L.) cover crop was under seeded in oats and spring barley in R6. In 2010, first year corn was grown in R6 and R8. The tillage treatments included no tillage, NT and mouldboard ploughing, MP. Topsoil structural quality was visually evaluated in early June and mid October. Minimal disturbed soil cores collected in early June were used for X-ray CT scanning and to quantify water content and porosity. Soil friability was determined on the soil samples using a drop shatter test. Crop yield was determined and correlated to the soil quality estimates. We found significant effect of both rotation and tillage on visual soil structure at both times of assessment. Poor soil structure was found for NT except when combined with a diverse crop rotation (R6). The soil core pore characteristics data also displayed a significant effect of tillage but only a weak insignificant effect of rotation. The drop shatter results were in accordance with the visual assessment data. Crop yield correlated significantly with the visual soil structure scores. We conclude that a diverse crop rotation was needed for an optimal performance of NT for the studied soil.